PELARANGAN AKITIVITAS JAMA’AT AHMADIYAH INDONESIA DALAM PERSPEKTIF HUKUM DAN HAM (Mengkaji Legalitas Sk Gubernur Jawa Timur Nomor 188/94/Kpts/013/2011) - Haris, Ach. Faidi; Marwini, Marwini (UIN Sunan Kalijaga Yogyakarta, 2012)
Incidents of violence against followers of Ahmadiyah in Indonesia are still happening. The case of destruction, burning mosques, is an example of violence against the Ahmadiyah congregation as a form of denial of the existence of this group and its teachings. In response, the government issued a decree three ministers, namely the agreement (SKB) between the Ministry of Religious Affairs, Ministry of Interior and the Attorney General who in essence to limit the activities of Ahmadiyah congregation in Indonesia. However, the SKB is sometimes still vague, yet firmly, proven related conflicts as well Ahmadis continues unabated. Therefore, as a preventive measure so that the conflict does not recur, some regional heads decided to publish a Decree (SK) on the prohibition of activities of Ahmadiyah congregation Indonesia, one of which is a East Java Governor Decree No. 188/94/KPTS/013/2011 that contains a ban on Ahmadiyah activities in East Java, Indonesia. After the issuance of the decree, the pros and cons in the back sticking out, some people accused the decree is unconstitutional, legally flawed both formal and material, as well as violation of Human Rights (HAM). This Decree can’t be formally referred to as the Administrative Decision, because there are still elements that have not been met, namely individual elements. On the other hand, the decree has jurisdiction flawed, because the material on the issue of religion under the authority of the central government. In other words, the decree is not legally and irrevocably flawed because it still contains elements of authority.